'I Try Not to Be Dominant, but I'm a Lawyer!': Advisor Resources, Context, and Refugee Credibility. (8th January 2021) - Smith-Khan, Laura
Abstract: Credibility assessments are a key component of refugee status determination. However, the difficulties associated with these assessments make professional assistance important. This article examines qualitative interviews with eight Australian migration advisors, exploring the key resources they report drawing on when contributing to client credibility in refugee status determination processes. Participants make sense of these resources and their choices about how they mobilize them by explicitly situating them within institutional and policy contexts. The article concludes that individual advisors vary in their approaches based on their beliefs about the particular resources they can and should mobilize within this context. These beliefs and practices, and the resources and contexts underlying them, have implications for how advisors contribute to asylum-seeker credibility, and ultimately, for access to refugee protection.